2016
DOI: 10.1002/mnfr.201500634
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin supplementation enhances adult hippocampal neurogenesis and spatial memory in mice

Abstract: ASX supplementation enhanced AHN and spatial memory, and a DNA microarray approach provided, for the first time, novel molecular insights into ASX action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Other studies also reported that administration of astaxanthin [80 mg/kg/day, oral gavage for 10 weeks (Yang et al, 2019); 25 mg/kg/day, oral gavage for 10 weeks (4 day/week) (Zhou et al, 2015)] did not affect spatial learning and memory in a Morris water maze test in WT mice. However, a higher dose of astaxanthin (0.5% astaxanthin-containing diet) for 8 weeks enhanced neurogenesis and improved special memory in male WT C57BL/6J mice (Yook et al, 2016). These findings suggest that feeding of normal chow with 0.02% astaxanthin might not affect spatial learning and memory in a Barnes maze test in WT mice although normal chow with astaxanthin in doses higher than 0.02% might enhance learning and memory even in WT mice.…”
Section: Protective Mechanisms Of Astaxanthinmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies also reported that administration of astaxanthin [80 mg/kg/day, oral gavage for 10 weeks (Yang et al, 2019); 25 mg/kg/day, oral gavage for 10 weeks (4 day/week) (Zhou et al, 2015)] did not affect spatial learning and memory in a Morris water maze test in WT mice. However, a higher dose of astaxanthin (0.5% astaxanthin-containing diet) for 8 weeks enhanced neurogenesis and improved special memory in male WT C57BL/6J mice (Yook et al, 2016). These findings suggest that feeding of normal chow with 0.02% astaxanthin might not affect spatial learning and memory in a Barnes maze test in WT mice although normal chow with astaxanthin in doses higher than 0.02% might enhance learning and memory even in WT mice.…”
Section: Protective Mechanisms Of Astaxanthinmentioning
confidence: 84%
“…In the present study, the WT mice were fed only normal chow without 0.02% astaxanthin, but not normal chow with 0.02% astaxanthin. A previous study reported that feeding of 0.02% astaxanthin-containing diet for 8 weeks did not affect adult hippocampal neurogenesis in male WT C57BL/6J mice (Yook et al, 2016). Other studies also reported that administration of astaxanthin [80 mg/kg/day, oral gavage for 10 weeks (Yang et al, 2019); 25 mg/kg/day, oral gavage for 10 weeks (4 day/week) (Zhou et al, 2015)] did not affect spatial learning and memory in a Morris water maze test in WT mice.…”
Section: Protective Mechanisms Of Astaxanthinmentioning
confidence: 92%
“…The mice from the exercise groups ran following the appropriate running protocol (four weeks) below their VT (SI Appendix, Table S7). The mice received a nonpurified basal diet with either AX or a placebo (AstaReal powder 20F; AstaReal Co. Ltd) at concentrations of 0.5% (SI Appendix, Table S8) (32).…”
Section: Methodsmentioning
confidence: 99%
“…Among potential dietary supplements, we focused on astaxanthin (AX), a red carotenoid with various health benefits, including enhancement of cognition. AX has highly antioxidant and antiinflammatory properties, with reportedly strong neuroprotective effects (31), and it enhances AHN and spatial memory (32), suggesting that it also has beneficial effects equivalent to those of ME on hippocampal functions. Hence, we hypothesized that ME-enhanced hippocampal neurogenesis and memory might be further improved with dietary AX via mediation by a neurotrophic factor such as h-LEP.…”
mentioning
confidence: 99%
“…Recent studies [4,101] have reported on the direct relationship between the healthy effects of astaxanthin on human brain and promotion of neurogenesis and plasticity, two processes that significantly decrease with age [29] and lead to cognitive decline among elderly people. Although the molecular process has not been completely elucidated, astaxanthin promotes neurogenesis and improves behavioral performance in hippocampal-dependent tasks; this could represent the predominant mechanism induced by astaxanthin, acting on cognitive functions and neurodegeneration caused by AD [4].…”
Section: Astaxanthin Against Alzheimer Disease (Ad)mentioning
confidence: 99%